S5_Unit_3_Outcome_2

# S5_Unit_3_Outcome_2 - Higher Unit 3 Higher Outcome 2...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Higher Unit 3 Higher Outcome 2 www.mathsrevision.com Differentiation The Chain Rule Further Differentiation Trig Functions Further Integration Integrating Trig Functions www.mathsrevision.com T h e C h a in R ule fo r Diffe re ntia ting Higher Outcome 2 To differentiate composite functions (such as functions with brackets in them) we can use: www.mathsrevision.com dy dy du = dx du dx Example Differentiate y = ( x 2 + 3)8 then y = u 8 dy = 8u 7 du Let u = ( x 2 + 3) du = 2x dx dy = dx dy du du dx = 8u 7 2 x = 8( x 2 + 3)7 .2 x dy = 16 x( x 2 + 3)7 dx Higher You have 1 minute to 1. Differentiate outside the bracket. come up with the rule. Outcome 2 2. Keep the bracket the same. Good News ! 3. Differentiate inside the bracket. The Chain Rule for Differentiating There is an easier way. www.mathsrevision.com h '( x) = g '( f ( x)) f '( x) Differentiate h( x) = ( x 2 + 3)8 h '( x) = 16 x( x 2 + 3) 7 Let f ( x) = ( x 2 + 3) then g ( x) = x8 g ( f ( x )) = ( x 2 + 3)8 g '( f ( x )) = 8( x 2 + 3) 7 h '( x ) = 16 x( x 2 + 3)7 f '( x ) = 2 x 1. Differentiate outside the bracket. Higher 2. Keep the bracket the same. Outcome 2 Example 3. Differentiate inside the bracket. Find f '( x) when f ( x) = The Chain Rule for Differentiating www.mathsrevision.com ( x 2 + 3) -4 5 4 f ( x) = 5( x + 3) 2 f '( x) = -20( x + 3) 2 -5 f '( x) = -20( x + 3) 2 -5 2x -40 x f '( x) = 2 ( x + 3)5 You are expected to do the chain rule all at once 1. Differentiate outside the bracket. Higher Outcome 2 Example 3. Differentiate inside the bracket. 2. Keep the bracket the same. The Chain Rule for Differentiating www.mathsrevision.com Find dy 1 when y = dx 2x -1 dy = (2 x - 1) dx - 1 2 3 dy 1 = - ( 2 x -1) 2 2 dx 2 dy = - dx 1 (2 x - 1) 3 2 The Chain Rule for Differentiating Higher Example 3 Outcome 2 2 5 If f ( x) = (3 x - 2 x + 1) , find the value of f '(0) www.mathsrevision.com Let f '( x) = 5(3 x - 2 x + 1) (9 x - 4 x) 3 2 4 2 Let f '(0) = 5(3 - 2 + 1) 4 0) 0 0 (9 0 3 2 4 2 f '(0) = 0 The Chain Rule for Differentiating Functions Higher Example Outcome 2 1 where x = 3 2x -1 Find the equation of the tangent to the curve y = www.mathsrevision.com The slope of the tangent is given by the derivative of the equation. y= 1 2x -1 Rearrange: y = ( 2 x - 1) -1 Use the chain rule: dy -2 = - 1( 2 x - 1) 2= dx 1 y= 5 and dy -2 = dx 25 -2 ( 2 x - 1) 2 Where x = 3: -2 1 We need the equation of the line through 3, with slope 5 25 The Chain Rule for Differentiating Functions Higher Outcome 2 1 -2 y = ( x - 3) - 5 25 -2 1 ( x - 3) + = 25 5 -1 5 (2 x - 6) + 25 25 Remember y b = m(x a) www.mathsrevision.com y= y= -1 (2 x - 1) 25 Is the required equation The Chain Rule for Differentiating Functions Higher Outcome 2 Example In a small factory the cost, C, in pounds of assembling x components in a month is given by: 1000 C ( x) = x + 40 , x 2 www.mathsrevision.com x 0 Calculate the minimum cost of production in any month, and the corresponding number of components that are required to be assembled. Minimum occurs where dC = 0, so differentiate dx 2 Rearrange 25 C ( x) = + = 40 x x 25 1600 + x x 2 The Chain Rule for Differentiating Functions Higher Outcome 2 2 dC d 25 = + 1600 x = x dx dx d 25 1600 + x dx x 25 25 3200 + 1 - 2 x x x 2 www.mathsrevision.com Using chain rule 25 25 = 1600 2 + 1 - 2 x = x x or 25 1 = - 2 0 x dC 25 = 0 where + 0 x = dx x i.e. where x 2 = -25 or x 2 = 25 We must have x>0 No real values satisfy x 2 = -25 We must have x = 5 items assembled per month The Chain Rule for Differentiating Functions Higher Outcome 2 Is x = 5 a minimum in the (complicated) graph? www.mathsrevision.com dC 25 25 = 3200 + 1 - 2 = 0 when x = 5 x dx x x Is this a minimum? Consider the sign of dC dx when x > 5 and x < 5 For x < 5 we have (+ve)(+ve)(ve) = (ve) For x = 5 we have (+ve)(+ve)(0) = 0 For x > 5 we have (+ve)(+ve)(+ve) = (+ve) Therefore x = 5 is a minimum x = 5 The Chain Rule for Differentiating Functions Higher Outcome 2 The cost of production: www.mathsrevision.com 25 C ( x) = 1600 + , x x 25 = 1600 + 5 5 2 2 x=5 = 1600 ( 10 ) 2 = 160,000 Expensive components? Aeroplane parts maybe ? Calculus Revision Differentiate ( x + 2)5 5( x + 2) 4 1 5( x + 2) 4 Chain rule Simplify Back Quit Next Calculus Revision Differentiate (5 x - 1)3 3(5 x - 1) 2 5 15(5 x - 1) 2 Chain Rule Simplify Back Quit Next Calculus Revision Differentiate (5 x 2 - 3x + 2) 4 4(5 x - 3x + 2) ( 10 x - 3) 2 3 Chain Rule Back Quit Next Calculus Revision Differentiate (7 x - 1) 5 2 Chain Rule 5 (7 x - 1) 2 3 2 7 3 2 Simplify 35 (7 x - 1) 2 Back Quit Next Calculus Revision Differentiate (2 x + 5) - 1 2 Chain Rule 1 - (2 x + 5) 2 - 3 2 2 Simplify -(2 x + 5) - 3 2 Back Quit Next Calculus Revision Differentiate Straight line form 3x - 1 ( 3x - 1) 1 2 1 2 Chain Rule ( 3x - 1) 3 2 - 1 2 1 2 3 Simplify ( 3x - 1) - Back Quit Next Calculus Revision Differentiate f ( x) = (8 - x ) 1 2 1 3 2 Chain Rule f ( x) = (8 - x 3 ) 3 - 2 - 1 2 ( -3 x 2 ) - 1 2 Simplify f ( x) = x 2 (8 - x 3 ) Back Quit Next Calculus Revision Differentiate f ( x) = ( 5 x - 4 ) 1 2 Chain Rule f ( x) = 1 2 ( 5x - 4) - 1 2 5 Simplify f ( x) = 5 2 ( 5x - 4 ) - 1 2 Back Quit Next Calculus Differentiate (x 5 2 Revision 4 + 3) Straight line form 5( x 2 + 3) -4 -20( x 2 + 3) -5 2 x -40 x( x 2 + 3) -5 Chain Rule Simplify Back Quit Next Calculus Differentiate 1 2x -1 Revision Straight line form (2 x - 1) 1 - (2 x - 1) 2 - 1 2 3 2 Chain Rule - 2 3 2 Simplify -(2 x - 1) - Back Quit Next Trig Function Differentiation Higher Outcome 2 www.mathsrevision.com The Derivatives of sin x & cos x d (sin x) = cos x dx d (cos x) = - sin x dx Trig Function Differentiation Higher Example 2 f ( x) = 2cos x + sin x . 3 Outcome 2 Find f '( x) www.mathsrevision.com d d 2 f '( x) = (2cos x) + sin x dx dx 3 d [ f ( x) + g ( x)] = dx df dg + dx dx =2 d 2 d (cos x) + ( sin x ) dx 3 dx d dg c.g ( x) = c dx dx 2 f '( x) = -2sin x + cos x 3 Trig Function Differentiation Higher Example Differentiate Outcome 2 4 - x 3 cos x with respect to x 3 x Simplify expression where possible www.mathsrevision.com 4 - x cos x = 4 x -3 - cos x x3 3 d (4 x -3 - cos x) = dx = -12 x -4 - (- sin x) = -12 x -4 + sin x x 4 sin x - 12 = x4 d d 4 x -3 - (cos x) dx dx Restore the original form of expression Higher The Chain Rule for Differentiating 1. Differentiate outside the bracket. Trig Functions Outcome 2 2. Keep the bracket the same. 3. Differentiate inside the bracket. www.mathsrevision.com Worked Example: dy = cos dx Differentiate y = sin(4 x) dy = cos 4 x du dy = cos 4 x 4 dx dy = 4cos 4 x dx Higher Example The Chain Rule for Differentiating Trig Functions Outcome 2 Find www.mathsrevision.com dy when y = cos 4 x dx dy = (cos x) 4 dx dy = 4(cos x)3 (-sin x) dx dy = -4sin x cos3 x dx Higher Example The Chain Rule for Differentiating Trig Functions Outcome 2 Find www.mathsrevision.com dy when y = sin x dx y = (sin x) 1 2 1 - dy 1 = (sin x) 2 cos x dx 2 dy cos x = dx 2 sin x Calculus Differentiate 2 2 cos x + sin x 3 2 -2sin x + cos x 3 Revision Back Quit Next Calculus Revision Differentiate -3cos x 3sin x Back Quit Next Calculus Revision Differentiate cos 4 x - 2sin 2 x -4sin 4 x - 4 cos 2 x Back Quit Next Calculus Revision Differentiate cos x -4 cos x sin x 3 4 Back Quit Next Calculus Revision Differentiate sin x (sin x) 1 (sin x) 2 - 1 2 Straight line form Chain Rule 1 2 cos x - 1 2 Simplify 1 cos x(sin x) 2 1 2 cos x sin x Next Back Quit Calculus Revision Differentiate - sin(3 - 2 x) - cos(3 - 2 x) ( -2) 2 cos(3 - 2 x) Chain Rule Simplify Back Quit Next Calculus Differentiate cos 5 x 2 Revision Straight line form 1 cos 5x 2 1 sin 5 x 2 5 sin 5x 2 Chain Rule 5 Simplify Back Quit Next Calculus Revision Differentiate f ( x) = cos(2 x) - 3sin(4 x) f ( x) = -2sin(2 x) - 12 cos(4 x) Back Quit Next Calculus Differentiate y = 2 sin ( Revision x- 6 ) Chain Rule dy = 2 cos x - 6 dx dy = 2 cos x - 6 dx ( ) ) 1 Simplify ( Back Quit Next Calculus Revision Differentiate f ( x) = cos 2 x - sin 2 x f ( x) = -2 cos x sin x - 2 sin x cos x f ( x) = -4 cos x sin x Chain Rule Simplify Back Quit Next You have 1 minute to Integrating Composite Functions come up with the rule. Higher Outcome 2 Harder integration www.mathsrevision.com (3 x - 7) dx = 4 we get (3 x - 7)5 +c 15 (ax + b) n+1 (ax + b) n dx = +c a(n + 1) (3 x - 7) dx = 4 (3 x - 7) 4+1 +c = 3(4 + 1) (3 x - 7)5 +c 15 Integrating Composite Functions 2. Divide by new power. Higher 1. Add one to the power. 3. Compensate for bracket. Outcome 2 www.mathsrevision.com (ax + b) n dx = Example : (ax + b) n+1 +c a (n + 1) dt (4t - 2) 4 Evaluate (4t - 2) -4 dt = (4t + 2) -3 (4t + 2) -3 -3 (4t + 2) -3 4 3) (- (4t - 2) -3 =- +c 12 Integrating Composite Functions Higher 1. Add one to the power. 2. Divide by new power. Outcome 2 Example3. Compensate for bracket. www.mathsrevision.com Evaluate (u - 3) -2 du (u - 3) -1 -1 (u - 3) -1 +c 1 1) (- (u - 3) -1 (u - 3) -1 1 -2 (u - 3) du = +c = - +c -1 (u - 3) You are expected to do the integration rule all at once Integrating Composite Functions Higher Example Outcome 2 Evaluate 2 1 (2 x + 1)3 dx www.mathsrevision.com 2 + 1) 4 1 + 1) 4 (2 (1 x + 1) (2 - 8 8 = 8 1 4 2 = 68 Integrating Composite Functions Higher Example Outcome 2 Evaluate www.mathsrevision.com 4 -1 4 -1 (3 x + 4) dx 4 3 2 (3 x + 4) dx = 3 2 5 x + 4) 2 (3 = 5 3 2 -1 2(3 x + 4) 15 5 2 -1 4 5 5 2 2 2(3 4 + 4) 2(3 ( -1) + 4) = - = 15 15 682 5 1. Add one to the power. 2. Divide by new power. Higher Integrating Functions Outcome 2 Example 3. Compensate for bracket. www.mathsrevision.com Find f ( x) given f '( x) = ( 2 x - 1) 3 and f (1) = 2 f ( x) = So we have: ( 2 x - 1) ( 2 x - 1) dx = 3 Integrating 4 8 +c 16 +c= 8 f (1) = 2 = ( 2 1 - 1) + c = 8 4 1 +c = 8 Giving: 1 15 c = 2- = 8 8 f ( x) = ( 2 x - 1) 8 4 15 + 8 Calculus Revision Integrate (5 + 3 x) 2 dx (5 + 3x) +c 3 3 3 Standard Integral (from Chain Rule) 1 3 (5 + 3 x) 9 +c Back Quit Next Calculus Revision Integrate 1 dx 2 (7 - 3 x) (7 - 3 x) dx -2 Straight line form (7 - 3 x) -1 +c ( -1) ( -3 ) 1 (7 - 3 x) -1 3 +c Back Quit Next Calculus Revision 1 Find 0 (2 x + 3) dx 6 Use standard Integral (from chain rule) x + 3) (2 7 2 0 7 1 + 3) 7 + 3) 7 (2 (0 - 14 14 7 7 5 3 - 14 14 5580.36 - 156.21 5424 (4sf) Back Quit Next Calculus 1 Integrate 0 dx Revision 1 2 ( 3x + 1) 1 Straight line form 2 3 ( 3x + 1) 0 1 ( 3x + 1) 0 - 1 2 dx 2 - ( 3 + 1) 3 3 x + 1) ( 1 3 2 1 2 0 1 2 3 ( 0 + 1) 2 3 2 2 - 4 1 3 3 4 2 - 3 3 Back Quit Next Calculus Revision 2 Find 1 ( 2 x + 1) 3 dx 1 2 Use standard Integral (from chain rule) 2 x + 1) ( 4 2 4 4 + 1) 4 2 + 1) 4 ( ( - 4 2 4 2 4 4 5 3 - 8 8 68 Back Quit Next Calculus 0 Evaluate -3 (2 x + 3) 2 0 Revision Use standard Integral dx (from chain rule) x + 3) (2 3 2 -3 3 (2(0) + 3)3 -3) + 3)3 (2( - 6 6 27 27 + 6 6 54 6 27 - 27 - 6 6 9 Back Quit Next Calculus 1 Evaluate Revision 0 3 2 1 + 3x 0 3 dx 1 0 1 ( 1 + 3x ) dx 2 9 2 9 1 2 ( 1 + 3 x ) 3 3 2 2 9 1 3 2 1 + 3x ) 2 ( 9 0 ( 1 + 3x 0 3 ) 1 ( 2 1 + 3(1) - 9 ) ( 1 + 3(0) 3 ) ( ) 2 4 - 9 3 ( ) 1 3 16 2 - 9 9 14 9 1 Quit 5 9 Back Next Calculus p Revision Find p, given 1 p x dx = 42 2 x = 42 3 1 3 2 p x 1 1 2 dx = 42 2 3 p3 2 3 p - 3 2 2 (1) 3 3 2 = 42 - 2 3 = 42 2 p3 - 2 = 126 p= (2 1 12 3 p3 = 64 p 3 = 642 = 212 ) = 16 Back Quit Next Calculus dy = 6 x 2 - 2 x passes through the point (1, 2). A curve for which dx Express y in terms of x. Revision 6 x3 2 x 2 y= - +c 3 2 Use the point y = 2 x3 - x 2 + c 2 = 2(-1)3 - (-1) 2 + c c=5 y = 2 x3 - x 2 + 5 Back Quit Next Calculus Given the acceleration a is: 1 Revision a = 2(4 - t ) 2 , 0 t 4 a= dv dt If it starts at rest, find an expression for the velocity v where dv = 2(4 - t ) dt 4 v=- 3 4 0=- 3 1 2 v= 2(4 - t ) 3 2 3 2 ( -1) +c 3 4 v = - (4 - t ) 2 + c 3 ( 4-t 3 ) 3 +c Starts at rest, so v = 0, when t = 0 32 0= - +c 3 32 c= 3 4 0=- 3 4 3 ( 4) 3 2 3 +c ( 4) +c v = - (4 - t ) + 32 3 Back Quit Next Integrating Trig Functions Higher Outcome 2 www.mathsrevision.com d (sin x) = cos x dx d (cos x) = - sin x dx Integration is opposite of differentiation cos x dx = sin x + c sin x dx = - cos x + c Worked Example ( 3sin x - 1 cos x ) dx = 2 - 3cos x - 1 sin x + c 2 1. Integrate outside the bracket Higher Integrating Trig Functions 2. Keep the bracket the same 3. Compensate for inside the bracket. Special Trigonometry Integrals are Outcome 2 www.mathsrevision.com cos( ax + b) dx = sin( ax + b) dx = Worked Example 1 sin( ax + b) + c a 1 - cos( ax + b) + c a sin(2 x + 2) dx = 1 - cos(2 x + 2) + c 2 1. Integrate outside the bracket 2. Keep the bracket the same Higher Integrating Trig Functions Outcome 2 Example Compensate for inside the bracket. 3. www.mathsrevision.com Evaluate ( sin 5t + cos(-2t ) ) dt Integrate 1 1 - cos5t + sin 2t + c 5 2 Break up into two easier integrals sin(5 co t )dt + s(-2t ) dt = 1. cos( - ) = cos cos + sin sin Integrate outside the bracket Higher Outcome 2 Example Compensate for inside the bracket. 3. 2. Keep the bracket the same 2 Integrating Trig Functions www.mathsrevision.com Evaluate 3cos - 2 x dx 2 4 Rearrange 2 4 Integrate 2 4 3cos - 2 x dx 2 3sin 2x dx = 2 3 - 2 cos 2 x 4 3 - cos = cos 2 - 2 2 2 4 3 = - ( -1 - 0 ) 2 3 = 2 Integrating Trig Functions (Area) Higher y1 y = - sin x y = cos x Example Outcome 2 0 The diagram shows the graphs of y = sin x and y = cos x -1 x A 2 www.mathsrevision.com a) Find the coordinates of A b) Hence find the shaded area The curves intersect where tan x = -1 x = tan (-1) = -1 cos x = - sin x 90o S T 3 2 3 7 and 4 4 180o A C 0o We want 0 x 3 x= 4 270o Integrating Trig Functions (Area) Higher Outcome 2 The shaded area is given by (top curve - bottom curve) dx 3 4 www.mathsrevision.com Area = 3 4 (cos x - (- sin x)) dx = 3 4 0 (cos x + sin x) dx 0 0 [ sin x - cos x ] 1 1 = + + 1 2 2 3 3 = sin - cos 4 4 - ( sin 0 - cos 0 ) = 1+ 2 Integrating Trig Functions Higher Example b) Hence find cos3 x Outcome 2 a) By writing cos3 x as cos(2 x + x) show that cos3 x = 4cos 3 x - 3cos x www.mathsrevision.com cos(2 x + x) = cos 2 x cos x - sin 2 x sin x Remember cos(x + y) = = (cos 2 x - sin 2 x) cos x - (2sin x cos x)sin x = (cos 2 x - sin 2 x) cos x - 2sin 2 x cos x = cos3 x - 3sin 2 x cos x = cos3 x - 3 ( 1 - cos 2 x ) cos x cos3 x = 4cos3 x - 3cos x Integrating Trig Functions Higher Outcome 2 As shown above www.mathsrevision.com 3 cos3 x = 4cos x - 3cos x 3 1 cos x = (cos3 x + 3cos x) 4 1 (cos3 x + 3cos x) dx = 4 3 1 1 + sin 3 x + 3sin x c 4 3 1 cos x dx = ( sin 3 x + 9sin x ) + c 12 Calculus Revision Find 2 sin t dt 7 2 - cos t + c 7 Back Quit Next Calculus Revision Find 3cos x dx 3sin x + c Back Quit Next Calculus Revision Find -2sin d 2 cos + c Back Quit Next Calculus Revision Integrate (6 x 2 - x + cos x) dx Integrate term by term 6 x3 x 2 - + sin x + c 3 2 Back Quit Next Calculus Revision Find 1 3sin x - cos x dx 2 1 -3cos x - sin x + c 2 Integrate term by term Back Quit Next Calculus Revision Find sin 2 x - cos x - dx 3 4 1 1 - cos 2 x - sin x - 3 2 3 4 + c Back Quit Next Calculus Revision ,1 The curve y = f ( x) passes through the point 12 f ( x) = cos 2 x f ( x) = 1= 1= 1 2 Find f(x) use the given point ,1 12 1 sin 2 x 2 +c 1 sin 2 2 1 2 12 +c c= 3 4 1= 1 sin 2 6 + c sin = 1 6 2 1 sin 2 x 2 +c f ( x) = + 3 4 Back Quit Next Calculus f ( x) = sin(3 x) If Revision passes through the point ( 9 , 1 ) ) 1= 1 - 3 1 2 y = f ( x) express y in terms of x. Use the point f ( x) = 1= 1 - cos(3 x) + c 3 ( 9 , 1 1 - cos 3 3 7 6 + c 9 1 3 1= 1 - cos 3 3 7 6 + c +c =c y = - cos(3x ) + Back Quit Next Calculus Revision dy = 3sin(2 x) passes through the point A curve for which dx 3 y = - cos(2 x) + c Find y in terms of x. 2 ( 5 , 12 3 ) Use the point 3=- 3 2 ( 5 , 12 3 ) 3 = - cos(2 3=- 3 c= 4 3 2 5 )+c 12 5 cos( ) + c 6 3 3 - + c 2 2 3= 3 3 +c 4 4 3 3 3 - =c 4 4 y = - cos(2 x) + 3 2 3 4 Back Quit Next ...
View Full Document

## This note was uploaded on 02/13/2012 for the course MAT 205 math 205 taught by Professor Google during the Spring '10 term at University of Phoenix.

Ask a homework question - tutors are online